Placebo and Non-specific Effects in Reconsolidation-Based Treatment for Arachnophobia - Elsey, James W. B.; Kindt, Merel (Frontiers in Psychiatry, 2021)
The idea that maladaptive memories may be rendered susceptible to interference after reactivation raises the possibility of reactivating and neutralizing clinically-relevant emotional memories. In this study, we sought to investigate the feasibility of such a “reconsolidation-based” intervention for arachnophobia, drawing upon previous research that successfully reduced fear of spiders in a subclinical sample. In Experiment 1, we piloted several reactivation procedures for conducting a reconsolidation-based treatment for arachnophobic individuals. All procedures involved some form of brief exposure to a fear-provoking spider, followed by the administration of 40 mg propranolol. In Experiment 2, we conducted a double-blind, placebo-controlled assessment of one procedure tested in Experiment 1. In Experiment 1, we found that most reactivation procedures produced drops in self-reported fear of spiders from pre- to post-treatment, including fear declines that were apparent up to 6- and even 14-months later. However, in Experiment 2, we found no evidence that the participants receiving propranolol were better off than those who received placebo. While our findings are limited by the small sample sizes used, they nevertheless show a different pattern of responses than was observed in a previous reconsolidation-based intervention for subclinical spider fearful participants. Alterations to the protocol made to accommodate the clinical participants may have led to greater opportunities for non-specific effects (e.g., exposure, placebo effects) to drive change in the participants. Our findings highlight both the challenges of translating reconsolidation-based procedures into clinical interventions, as well as the importance of controls for non-specific effects in reconsolidation-based research.